The impact of trade barriers on Malaysia export performance in US market / Afiza Syaireen Othman - Othman, Afiza Syaireen (Faculty of Business and Management, 2013)
This research is conducted to investigate the impact of the trade barriers toward Malaysia export performance. The study focuses on the US market. The trade barriers being investigate are the balance of payment, population, exchange rate and inflation rate. The relationship between dependent variable and independent variables is being analyzed. The findings of the research shown there is significant relationship between population and Malaysia export performance. Matyas (1997) finds that population has a tendency to increase trade and the level of specialization by producing gains from specialization. In addition, exchange rate has seen to be no significant relationship with Malaysia export performance. According to Bacchetta and Van Wincoop (2000), the trade is not significantly affected by the exchange rate uncertainty. However the other independent variables which are balance of payment and inflation rate also seen to have no significant relationship between Malaysia export performances. Researchers recommend Malaysia Universities or colleges can encourage students involve in international trade by providing them with entrepreneurship programed. Researchers also recommend future researcher to study and investigate more details on the trade barriers.